Hemodynamic, management, and outcomes of patients admitted to emergency department with heart failure. Issue 1 (December 2016) - Claret, Pierre-Géraud; Stiell, Ian; Yan, Justin; Clement, Catherine; Rowe, Brian; Calder, Lisa; Perry, Jeffrey
Abstract Background Heart failure is one of the leading reasons for hospitalization in developed countries. Our goal was to describe the hemodynamic vital signs (heart rate and systolic blood pressure) of patients presenting to the emergency department (ED) with heart failure and to describe the frequency of adverse events for patients presenting with various heart rate and systolic blood pressure values. Method We conducted two prospective cohort studies of heart failure conducted at six Canadian teaching hospital sites and this study was a secondary analysis of these data. The primary outcome was serious adverse events defined as death from any cause within 30 days of the ED visit or any complication following within 14 days of the index ED visit. Results We included a convenience sample of adults > 50 years of age who presented with acute shortness of breath or new-onset heart failure. In total, 1, 638 patients were included in this analysis. Patients with heart rates < 50 % MHR (maximal heart rate) and systolic blood pressure (SBP) > 140 mmHg had the lowest rate of serious adverse events (6 %). patients with heart rates > 75 % MHR had the highest rate of serious adverse events, regardless of the SBP. Among patients with heart rates > 75 % MHR, the proportion of serious adverse events decreased as SBP increased (30 % when SBP < 120 mmHg, 24 % when SBP between 120 and 140 mmHg, and 21 % when SBP > 140 mm Hg). Patients with heart rates < 50 % MHR and with SBP > 140 mm Hg had the lowest rate of admissions to hospital (38 %). Conclusions We found a relatively high frequency of serious adverse events among patients who present to the ED with heart failure, particularly among the patients having low systolic blood pressure and high heart rate.